The Meaning and Essence of the Islamic Education Curriculum - Dudus Ruhimat; Maspuroh; Nadila; Siti Holipah; Siti Nurkasyifah (Penerbit Hellow Pustaka, 2025)
In the perspective of Islamic educational philosophy, the curriculum is seen as a holistic guide rooted in divine values, with the Qur'an and Hadith as its primary sources. Ontologically, the curriculum includes all educational components aimed at developing human potential in its entirety, encompassing cognitive, affective, psychomotor, and spiritual aspects. Islamic epistemology asserts that Allah is the ultimate educator, while humans are learners who must submit to His teachings. From an axiological perspective, the Islamic curriculum aims not only for academic success but, more importantly, for the development of noble character (akhlaq), with a primary focus on devotion to Allah.